Relationship between breast arterial calcification and lipid profile, plasma atherogenic index, Castelli's risk index and atherogenic coefficient in premenopausal women. (June 2016) - Yıldız, Abdulmelik; Seçen, Özlem; Yıldız, Cennet; Çiçekçi, Mehtap
Abstract: Objective: The aim of this study was to investigate the relationship between the breast arterial calcification (BAC) and the plasma atherogenic index (PAI), atherogenic coefficient (AC), Castelli risk index-I (CRI-I) and Castelli risk index-II (CRI-II). Methods: This retrospective study included 60 premenopausal women aged over 40 years with BAC on mammograms and control group of 60 women without BAC. Serum glucose, triglyceride (TG), low-density lipoproteincholesterol (LDLc), high-density lipoprotein-cholesterol (HDLc), and total cholesterol (TC), levels were measured. Lipid indices were calculated using the appropriate formula. Results: LDLc, non-HDLc levels were significantly higher, HDLc levels were siginificantly lower in patient group compared to the control group (p = 0.007, p = 0.027, and p = 0.014, respectively). Patient group had significantly higher PAI, AC, CRI-I and CRI-II levels than the control group (p = 0.003, p = 0.002, p = 0.002 and p = 0.003, respectively). A significant positive correlation was found between BAC and PAI, AC, CRI-I and CRI-II (r = 0.267 and p = 0.003, r = 0.282 and p = 0.002, r = 0.282 and p = 0.002, r = 0.271 and p = 0.003, respectively). LDLc and non-HDLc were positively correlated whereas HDLc was negatively correlated with the BAC (r = 0.188 and p = 0.039, r = 0.202 and p = 0.027, r = − 0.223 and p = 0.014, respectively). Conclusion: BAC is a valuable tool for the prediction of deranged lipid profile. Dyslipidemia, PAI, AC, CRI-I and CRI-II are risk factors for the development of atherosclerosis. Our results indicate that BAC is potentially useful tool for the detection of dyslipidemia and early atherosclerosis in premenopausal women.